BAHASA DALAM BINGKAI TRINITAS SUCI PIERRE BOURDIEU - Hendra Hendra (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2020)
Language is a basic human need because it will help them to find their existence. The purpose of writing this article is to reveal the relationship between language and culture within the framework of Pierre Bourdieu's theory regarding habitus, the field, and capital. The purpose of this paper is to reveal the relationship between language and culture in everyday life. The research method that used in this article is a study of literature with classification and coding analysis and data interpretation followed by the conclusion arrangement. The finding in this study a Language then arises as a result of the construction of a culture and also constructed the culture itself: (1) language as an active and passive marker (gender structure); (2) language as a link between someone and something else (position mark); (3) language as sign of class and a strategy for discourse; and (4) language as a sign of change. Language is frame and framing the culture.